2017
DOI: 10.1002/art.39995
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for Colchicine‐Resistant Familial Mediterranean Fever: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: In this randomized controlled trial, anakinra appears to be an effective and safe treatment for colchicine-resistant FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 42 publications
4
103
0
13
Order By: Relevance
“…32 Second, familial Mediterranean fever that is refractory to colchicine prophylaxis has been successfully treated with anakinra, an IL-1 blocking agent. 33 Third, the variability in the incidence of ERMF may be accounted for, in part, by IL-1ra gene polymorphisms. Two common variants located upstream of IL1RN, the gene encoding IL-1ra, are the strongest known genetic determinants of increased soluble IL-1ra concentration.…”
Section: Discussionmentioning
confidence: 99%
“…32 Second, familial Mediterranean fever that is refractory to colchicine prophylaxis has been successfully treated with anakinra, an IL-1 blocking agent. 33 Third, the variability in the incidence of ERMF may be accounted for, in part, by IL-1ra gene polymorphisms. Two common variants located upstream of IL1RN, the gene encoding IL-1ra, are the strongest known genetic determinants of increased soluble IL-1ra concentration.…”
Section: Discussionmentioning
confidence: 99%
“…8 9 For patients who are resistant or intolerant to colchicine, anti-IL-1 therapy is a safe and effective alternative. [10][11][12][13] Colchicine prevents not only FMF attacks but also disease-associated complications such as amyloid A amyloidosis, a severe manifestation with poor prognosis. 9 However, it is crucial to establish a timely and correct diagnosis of FMF before committing to daily, lifelong treatment.…”
Section: Autoinflammatory Disordersmentioning
confidence: 99%
“…Fever attacks and chest pain were reduced during Anakinra treatment but reappeared upon discontinuation (Calligaris et al, 2008). Recent results of a double-blind, placebo-controlled, randomized study involving 14 colchicine-resistant FMF patients showed that those who received Anakinra daily at a subcutaneous dosage of 100 mg had significantly less fever attacks per month (1.7 vs. 3.5 in the placebo group) (ClinicalTrials.gov Identifier: NCT01705756) (Ben-Zvi et al, 2017). …”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%